Insights into reproductive dynamics and feeding biology of Sphyraena putnamae Jordan and Seale, 1905 exploited in the Indian EEZ: stock dynamics of Sphyraena putnamae - R. Vinothkumar,; Subal Kumar Roul,; Ajay D. Nakhawa,; H. M. Manas,; S. Surya,; C. Anulekshmi ,; Shubhadeep Ghosh,; K. M. Rajesh,; A. Margaret Muthu Rathinam,; E. M. Abdussamad,; Prathiba Rohit, (Indian Journal of Fisheries, 2024)
The sawtooth barracuda Sphyraena putnamae, widely distributed in the Indo-Pacific region, isone of the commercially important barracuda species exploited by trawls in the Indian EEZ.The present study examined 2,135 S. putnamae collected during 2014-2020 from differentfish landing centres along the Indian coast, to elucidate their reproductive and feedingbehaviour. The fork length of sampled females and males varied from 12.5 to 130.9 cm and16.5 to 90.0 cm respectively. Negative allometric growth was observed with a significantdifference (p